Produção de videira 'Superior Seedless', cultivadas em diferentes tensões de água no solo - Souza, Essione Ribeiro [UNESP]; Pionório, José Anchieta de Assunção; Ribeiro, Valtemir Gonçalves; De Queiroz, Sérgio Oliveira Pinto (My University, 2013)
The aim of this study was to evaluate the total number of clusters per plant and the sugar concentration of Superior Seedless grapevine branches under different soil water tensions conditions. The statistical design was a randomized block with 4 treatments (a) control, b) 70 kPa tension, c) 50 kPa tension, d) 30 kPa tension, and 6 replications, each plot consisting of two plants. Soil moisture curves were plotted in laboratory and field conditions, potential bud fertility (carried out with the help of a 30x magnifier glass and collecting 17 branches in the primary arm of the plant with 15 buds each), actual fertility (given by the fertile buds to sprouted buds per plant ratio) and total sugars. Laboratory conditions helped stress to reach a -70 kPa level in just 21 days during the procedure to determine the retention curve in the laboratory. The different stress levels applied to the soil did not cause significant differences in the total number of clusters per plant. However, a -30 kPa stress showed a 68% reduction in water depth when compared to control and different soil water stress affected the carbohydrate percentage in branches of the Superior Seedless vine.

O objetivo deste trabalho foi avaliar o número total de cachos por planta e concentração de açúcares totais em ramos de videira ‘Superior Seedless’ submetidas a diferentes tensões de água no solo. O delineamento estatístico utilizado foi o de blocos casualizados com 4 tratamentos (a) Testemunha, b) tensão de 70 kPa, c) tensão 50 kPa, d) tensão de 30 kPa, e 6 repetições, sendo cada parcela constituída por duas plantas. Foram determinadas curvas de umidade de solo em laboratório e em campo, fertilidade de gema potencial (realizada sob lupa (aumento: 30 vezes), coletando-se 17 sarmentos no braço primário da planta, contendo 15 gemas cada), fertilidade real (utilizando-se a razão: número de gemas férteis pelo número total de gemas brotadas por planta) e açúcares totais. As condições laboratoriais favoreceram a chegada da tensão a -70 kPa em apenas 21 dias durante o procedimento de determinação da curva de retenção em laboratório. As diferentes tensões aplicadas ao solo não promoveram diferenças significativas quanto ao número total de cacho por planta. Contudo, a tensão de -30 kPa apresentou uma redução de 68% na lâmina de irrigação quando comparado com a testemunha e o percentual de carboidratos nos ramos da videira ‘Superior Seedless foi influenciado pelas diferentes tensões de água no solo.
Production vine 'Superior Seedless' cultured under different water stress conditions
Keywords: Irrigation; Management; Total sugars; concentration (composition); irrigation system; soil moisture; soil water; sugar; vine; water depth; water stress; water supply; water use